병원간호사의 근거기반 욕창예방간호실무 수행도 - 김애진; Kim Ae-jin; 정인숙; Jeong Ihn Sook (글로벌 건강과 간호, 2018)
Purpose: This study was aimed to identify the performance of pressure ulcer (PU) preventive practices based on the clinical nursing guideline of PU among hospital nurses. Methods: This descriptive survey research was conducted with 256 nurses from 9 selected hospitals located in the city of Busan. Data was collected with a structured questionnaire developed by the researcher based on the evidence-based pressure ulcer guideline, and analyzed with SPSS using descriptive statistics, t-test, one way ANOVA. Results: PU preventive practices were performed by 67.6% of all nurses. Nurses who had a education on PU management (p<.001), who were working at high level general hospitals or hospitals (p=.046), and who were working at wards having the PU guidelines (p=.012) showed higher performance of PU preventive practices than counterparts. Conclusion: The performance level was not satisfactory. Therefore, a PU management training program is highly recommended for clinical nurses to improve the performance on the PU preventive practices. And, it is also recommended to distribute clinical practice guidelines on PU management and implement them into the hospital wards in order for nurses to efficiently perform the PU management in the clinical settings.